Pattern of emergency department visits by elderly patients: study from a tertiary care hospital, Karachi - Fayyaz, Jabeen (BioMed Central, 2013)
BACKGROUND: Worldwide the proportion of elderly people in the population is increasing. Currently in Pakistan 7.3 million people (5.6% of total population) are more than 60 years old. This age shift has emerged as an important health issue and is associated with an increased utilization of emergency services by the elderly. We carried out this study to assess the pattern of elderly patients (>60 years) who visit emergency departments in comparison to young adults (18–60 years). METHODS: Data was collected retrospectively of patients aged 18 years or more who visited the Emergency Department (ED) of Aga Khan University Hospital, Karachi (AKUH) during September, 2009 to September, 2011. The data collection sheet included patient’s demographic information, triage category, reason for visit, clinical presentation, ED length of stay, day and time of presentation and their disposition. Data was entered and analyzed using SPSS version 19.0. Descriptive statistics were used to describe patient’s demographics. Chi-square (χ(2)) test was used as a test of significance to compare differences between groups for categorical data and t-test for continuous data. Multiple logistic regression analysis was done to find out the association between the patient characteristics and outcomes (admission and expiry). RESULTS: Almost 24% (n = 13014) of all adults (n = 54588) presenting to the ED were over the age of 60 years. More than 57% of elderly patients belonged to the high priority triage category compared to 35% in younger patients. Most of the elderly patients ( 27%) presented with nonspecific complaints followed by shortness of breath (13%) and fever (9%). The median length of stay (LOS) in the ED for elderly was 379 minutes (252 min in under-60 yrs patients) and they were more likely to get admitted to in-patient departments compared to younger patients (OR 1.7 95% CI 1.6-1.8). A high proportion of those admitted (20%) required intensive or special care. Mortality in elderly patients was 2.3% as compared to 0.7% in young adults. This was accompanied by a higher mortality risk in the elderly with an odds ratio of 2.3 (CI 2–2.5). CONCLUSION: Elderly ED users differ significantly from younger adults in terms of criticality on presentation, ED LOS and final disposition.